A Comparative Study of Saline-sodic, Sodic and Normal Soils in Relation to forest Growth of South Kheri Forest division, (U.P.) - Singh, K.; Sharma, S. K.; Singhal, R. M.; Samra, J. S.; Sharma, S. D. (Indian Forester, 1982)
A soils investigation was conducted in April. 1979 in some salt-affected and normal soils of South Kheri Forest division (U.P.) in order to compare (I) saline-sodie soils where all forest species have failed to grow, (ii) sodie soils having fair growth of some tolerant forest species, and (iii) Normal soils having good stand of natural sal forest. These soils vary widely in several morphological. Physical and chemical characteristics and accordingly, the forest species have shown varying growth response. In general, all forest species have failed to grow on CO3-CI type saline-sodic soils which are compact and indurated with cemented bed of CaCO3 (kankar) nodules mixed in clay pan, have drainage donditions very poor, pH>9.5, ESP>40 and EC> 4 m mhos/cm. Few lines on reclamation of these soils have also been suggested. Tendu (Diospyros tomentosa). Dhak (Butea monosperma) Mahus (Madlmca indica). Dudhi (Wrightia tomentosa). Jamun (Syzygium cumini) and Rohini (Mallotus philippinensis) are able to grow on CI-HCO3 type sodic soils having a maximum pH value 8.0. EC of saturation extract 4 m mhos/cm at 25Â°C and ESP 10 in top one metre deep soil but in subsoil tolerance of plants may go upto the values of pH 9.3, ESP 40 and EC 4. A good growth of sal (Shorea robbusta) is obtained in well drained nonsaline-nonsodic soils.